Aplikasi Pengenalan Huruf Hiragana dan Katakana Jepang Berbasis Android Menggunakan Kodular - Iwan Setiadi; Santi Widianti; Athaullah Afra Afratofani (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Japan is a country in Asia that has a quite unique culture. There is an influence of Japanese culture on various countries, one of which is Indonesia, such as Anime (Japanese videos and animation), Manga or Japanese comics, and typical Japanese food such as sushi, ramen and takoyaki. This makes many Indonesian people interested in learning Japanese. This Android-based application for recognizing Japanese Hiragana and Katakana letters called "Nihon" can meet the needs of Indonesian people who want to learn the basic Japanese language, namely hiragana and katakana. This application provides explanations in the form of words, vocabulary and sounds for each hiragana and katakana letter, and numbers and punctuation marks in Japanese. This application was made using the Kodular web. The results of the Android-based application for recognizing Japanese hiragana and katakana letters can help Indonesian people to know Japanese hiragana and katakana letters, numbers in Japanese, and punctuation in Japanese.